Investigating benefits realisation process for enterprise resource planning systems - Badewi, Amgad (Cranfield University, 2016)
This research aims to investigate the benefit realisation process for ERP systems so as to develop a benefit realization road map whereby organisations can realize the maximum potential of their ERP systems. This research covers two areas: mechanism of implementation and the destination to change (i.e. road map). It has been found that project management and benefits management approaches are necessary for recouping benefits from investing in Information Technologies (IT) projects. Thus, Project Benefits Governance Framework (PBGF) is developed, and later tested, by combining the two approaches for the sake of realising the expected benefits from investing in IT initiatives. Because ERP demands radical changes in organisations, the neo-institutionalisation theory was adopted to apply PBGF on ERP so that the ERP success is improved. The key connecting element between PM and BM in PGBF is the blueprint design. ERP orchestration framework is developed to show how investments in ERP resources and organisational complementary resources shall be orchestrated so that ERP benefits can be realised effectively. Thus, benefits are classified into three levels (automating, planning, and innovating benefits), and each level needs a specific blueprint. All of these blueprints constitute the ERP benefits road map. Each blueprint consists of attitudes, skills, organisation characteristics, technologies, and ERP department human resources competencies. Based on these results, ERP Business Innovation framework is developed and tested. ERP benefits maturity assessment tool is developed for assessing organisations’ status to show weaknesses and strengths in their ability to recoup different ERP benefits by benchmarking with the three blueprints. This research has contributed by integrating and institutionalising benefits management practices and project management practices. Moreover, it is novel in adapting the orchestration theory to understand how ERP resources shall be composed to achieve benefits efficiently. Finally, it demonstrates that ERP can be a source of innovation if the innovating benefits are managed deliberately.